9+2(x-6)=6-2(x-3)

Simple and best practice solution for 9+2(x-6)=6-2(x-3) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 9+2(x-6)=6-2(x-3) equation:


Simplifying
9 + 2(x + -6) = 6 + -2(x + -3)

Reorder the terms:
9 + 2(-6 + x) = 6 + -2(x + -3)
9 + (-6 * 2 + x * 2) = 6 + -2(x + -3)
9 + (-12 + 2x) = 6 + -2(x + -3)

Combine like terms: 9 + -12 = -3
-3 + 2x = 6 + -2(x + -3)

Reorder the terms:
-3 + 2x = 6 + -2(-3 + x)
-3 + 2x = 6 + (-3 * -2 + x * -2)
-3 + 2x = 6 + (6 + -2x)

Combine like terms: 6 + 6 = 12
-3 + 2x = 12 + -2x

Solving
-3 + 2x = 12 + -2x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '2x' to each side of the equation.
-3 + 2x + 2x = 12 + -2x + 2x

Combine like terms: 2x + 2x = 4x
-3 + 4x = 12 + -2x + 2x

Combine like terms: -2x + 2x = 0
-3 + 4x = 12 + 0
-3 + 4x = 12

Add '3' to each side of the equation.
-3 + 3 + 4x = 12 + 3

Combine like terms: -3 + 3 = 0
0 + 4x = 12 + 3
4x = 12 + 3

Combine like terms: 12 + 3 = 15
4x = 15

Divide each side by '4'.
x = 3.75

Simplifying
x = 3.75

See similar equations:

| 5x-(-3x)+4x^2= | | 145000=4000(q-2)+65000q | | 2(7-3x)=1/4 | | 13.33+y=27.33 | | 8x=6+5 | | -5x-2=-7x+10 | | 7.25y=-101.5 | | X+x+x=177 | | 135000=40(q-2)+9000q | | 2t^2-7t=4 | | 19m-38=21 | | 1.03x=6.18 | | (4k-5)(3k-2)=0 | | 19m-38=31 | | 3132=P(1+0.04*4) | | 24n=24 | | x=l-19l-l-11l | | 3-x=1/81 | | -4-3t-(-4)+t+(-6t)= | | 135000=9000(q-4)+80000q | | 0.1(x+60)+0.3x=10 | | -7x-3=85+x | | 2g+12=22-10g | | 6-tanx=2sec^2x | | x+34=2x+12 | | 3m+13=42-9m | | 3m+13=42-9 | | z^2-26z+169=0 | | 7-3x+6x=40 | | 4+m=-1 | | 2x^3+5x^2-98x+245=0 | | x^2+9x-2=5 |

Equations solver categories